What Obstetric Health Care Providers Need to Know About Measles and Pregnancy - Rasmussen, Sonja A. (Obstet Gynecol, 2015)
From January 1 to April 3, 2015, 159 people from 18 states and the District of Columbia were reported as having measles. Most cases are part of an outbreak linked to a California amusement park. Because measles was eliminated in the United States in 2000, most U.S. clinicians are unfamiliar with the condition. We reviewed information on the current outbreak, measles manifestations, diagnostic methods, treatment, and infection-control recommendations. To identify information on measles and pregnancy, we reviewed reports with 20 or more measles cases during pregnancy that included data on effects on pregnant women or pregnancy outcomes. These reports were identified through MEDLINE from inception through February 2015 using the following strategy: (((pregnan*) AND measles) AND English[Language]) NOT review[Publication Type]. Reference lists also were reviewed to identify additional articles. Pregnant women infected with measles are more likely to be hospitalized, develop pneumonia, and die than nonpregnant women. Adverse pregnancy outcomes, including pregnancy loss, preterm birth, and low birth weight, are associated with maternal measles; however, the risk of congenital defects does not appear to be increased. No antiviral therapy is available; treatment is supportive. Early identification of possible cases is needed so that appropriate infection control can be instituted promptly. The recent measles outbreak highlights the role that obstetric health care providers play in vaccine-preventable illnesses; obstetrician–gynecologists should ensure that patients are up to date on all vaccines, including measles-containing vaccines, and should recommend and ideally offer a measles-containing vaccine to women without evidence of measles immunity before or after pregnancy.